Effectiveness and efficiency of administrative appeal procedures - Moldovan, Octavian (Central European Public Administration Review, 2019)
The aim of this article is to evaluate the effectiveness and efficiency of (internal) administrative appeal in tax or fiscal matters in Romania, in comparison to the more time and resource consuming court action against an administrative decision imposing fiscal obligations. In order to evaluate the effectiveness and efficiency of administrative appeals, we analysed data from the reports and documents issued by the Romanian National Agency for Fiscal Administration (NAFA) regarding efficiency related indicators, as well as dispute settlements and the amount of collected tax as effectiveness criteria. Furthermore, data regarding the results of the administrative procedure is compared to the results of the judicial procedure in terms of the number of admitted legal actions that annulled fiscal obligations. The results show that at least in the 2013-2017 period, the administrative procedure was both inefficient and ineffective since, on average, less than 7% of fiscal disputes were solved/settled in favour of the appellant. Moreover, the procedure was rather time consuming - although the disputes should have been settled in 45 days, the answer was provided after 70 days. Hence, the administrative procedure is often seen as a mere stepping stone toward subsequent legal/court actions, with no possibility to provide a satisfactory solution and thus lessen the workload of the court. Surprisingly, the taxpayers seem to consider the courts as a more favourable/efficient means as more than half of legal actions brought against fiscal administrative acts were settled in favour of the taxpayer, i.e. the fiscal obligations were annulled. The effectiveness of the preliminary administrative procedure was further analysed from multiple perspectives pertaining to the players that have a direct or indirect legitimate interest in this procedure. These are (i) the courts, which should/could benefit from a reduced workload if the procedure was effective, (ii) the taxpayers filing administrative appeals, which could have a feasible alternative to the time and resource consuming judicial means, and (iii) the fiscal bodies that issued fiscal administrative acts or that must respond to the appeals. The fact that this procedure is a mandatory predecessor of the judicial one and not an alternative means of dispute resolution seems to significantly impede its efficiency and effectiveness. The results can serve as a basis to analyse and compare the respective data in other countries with similar legal and tax systems.
Keywords: administrative appeal procedure; effectiveness; efficiency; judicial procedure; Romania; tax disputes; tax/fiscal administration